2008
DOI: 10.1038/nature07320
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up organic integrated circuits

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
374
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 374 publications
(390 citation statements)
references
References 18 publications
13
374
2
1
Order By: Relevance
“…semiconductors showing large p-and n-type mobilities 1-4 , dielectrics and circuit methodologies providing low power consumption [5][6][7][8] and smart production methods suitable for flexible substrates [9][10][11][12] have been developed. Much attention has focussed on realizing electrically and environmentally stable OTFTs required to successfully implement complex systems such as radio frequency identification (RFID) tags 10,[13][14][15][16] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…semiconductors showing large p-and n-type mobilities 1-4 , dielectrics and circuit methodologies providing low power consumption [5][6][7][8] and smart production methods suitable for flexible substrates [9][10][11][12] have been developed. Much attention has focussed on realizing electrically and environmentally stable OTFTs required to successfully implement complex systems such as radio frequency identification (RFID) tags 10,[13][14][15][16] .…”
mentioning
confidence: 99%
“…Much attention has focussed on realizing electrically and environmentally stable OTFTs required to successfully implement complex systems such as radio frequency identification (RFID) tags 10,[13][14][15][16] . An avenue that has received far less attention, despite carrying tremendous promise, is the "controllable" manipulation of the transistor functionality beyond that of a switch or amplifier.…”
mentioning
confidence: 99%
“…[ 12 ] The trichlorosilane derivative ( 7b ) was more reactive and working monolayer fi eld effect transistors were fabricated in less than 10 h over large areas (4 cm 2 ) for long channel lengths (up to 100 µm).…”
Section: Fabrication Of Sams and Devicesmentioning
confidence: 99%
“…[ 14,16 ] The breakthrough was achieved when Smits et al reported a SAMFET molecule consisting of a monochlorosilane anchoring group separated from a quinquethiophene core by an alkyl spacer. [ 12 ] The molecule showed long range order when deposited onto a silicon dioxide surface and fi eld effect characteristics could be obtained over large areas for channel lengths up to 40 µm. SAMFETs have now been reported using phosphonic acid anchoring groups to covalently attach to aluminum oxide and alternative aromatic cores to create p-and n-type transistors over long channel lengths.…”
mentioning
confidence: 99%
See 1 more Smart Citation